Home is where the money goes: migration-related urban-rural integration in delta regions. (4th May 2018) - Szabo, Sylvia; Adger, William Neil; Matthews, Zoe
Abstract: The dominant movement of people in the mega-deltas of Asia is from agriculture-dominated rural areas to urban settlements, driven by growing opportunities, but resulting in new human development challenges. In this context, the present study aims to investigate whether remittance income leads to enhanced multiple dimensions of well-being in sending areas in deltas, by focusing on two delta regions with significant out-migration rates, Bangladeshi Ganges Brahmaputra and the Vietnamese Mekong deltas. The paper develops a conceptual framework that draws on existing migration theories and the aspirations and capabilities theories. Data from large scale sample household surveys (2010 Bangladesh Household Income and Expenditure Survey and 2012 Vietnam Living Standards Survey) are analysed through multilevel regression modelling to examine well-being outcomes in sending areas and links to remittance income. The results show that the temporal extent of internal and international migration is positively associated with remittances in both delta regions. The results also suggest that in both delta regions remittances have a significant positive effect on household well-being in the source rural areas, including overall income, investments in health, food security and access to sanitation. The study concludes that landscapes of urban and rural deltas are increasingly economically integrated which suggests greater resilience even for environmentally-at-risk tropical deltas.